An adaptive sliding mode actuator fault tolerant control scheme for octorotor system. (7th March 2019) - Ejaz, Fatima; Hamayun, Mirza Tariq; Hussain, Shariq; Ijaz, Salman; Yang, Shunkun; Shehzad, Naeem; Rashid, Aamir
In this article, an adaptive sliding mode control is used in the framework of fault tolerant control to mitigate the effects of actuator faults without requiring the actuator health information. Since unmanned aerial vehicles are being used in multiple fields such as military, surveillance, media, agriculture, communication and trading sector, therefore it is of vital importance to overcome the effects of actuator faults that can decline system performance and can even lead to some serious accidents. The proposed adaptive sliding mode control approach can handle actuator faults directly without requiring any faults information and adaptively adjusts controller gains to maintain acceptable level of performance. To validate the effectiveness of the proposed adaptive fault tolerant control scheme, it has been tested in simulations using non-linear Benchmark model of Octorotor system and its performance is compared with the optimal LQR control approach.